Distance and International Banking - Claudia M. Buch (Kiel Institute of World Economics (IfW), 2001)
If the technological revolution which has taken place over the past decades has lowered information costs and if information costs increase in distance, distance should – ceteris paribus – become less important in determining international bank lending. We are using a dataset on assets and liabilities of commercial banks from five countries (France, Germany, Italy, UK, US) in up to 50 host countries for the years 1983 through 1998 to test this hypothesis. For the European banks, distance has remained of the same importance it used to have. For the US, a declining importance of distance was found. Several interpretations of these findings are discussed.
Keywords: F21; G21; 330; cross-border banking; information costs; Bankgeschäft; international; Internationale Bank; Informationskosten; Wirtschaftsgeographie; Schätzung; Frankreich; Italien; Deutschland; Großbritannien; Vereinigte Staaten